Critical properties of refrigeration lubricants in modern refrigeration system: A review - Mohd Zaki, Sharif; Abd Aziz, Mohd Syafiq; Ismail, Mohd. Farid; Abdollah, Mohd Fadzli (Penerbit Akademia Baru, 2025)
Refrigeration systems are integral to industries like food preservation, industrial processes, and air conditioning. As the demand for energy-efficient and environmentally friendly solutions grows, refrigeration lubricants have become crucial for improving system performance. However, selecting the right lubricant remains challenging due to the varying operating conditions in modern systems. This paper reviews the key properties of refrigeration lubricants, such as thermal stability, viscosity, chemical compatibility, and wear protection, which significantly influence system efficiency. The purpose of this study is to evaluate the effectiveness of both traditional and synthetic lubricants, particularly focusing on their compatibility with low-global-warming-potential (GWP) refrigerants and the impact of nanoparticles on lubricant performance. A comparative analysis of mineral oils and synthetic lubricants like polyol ester (POE), polyalkylene glycol (PAG), and polyvinyl ether (PVE) was conducted. Methods include a review of existing literature and performance data on lubricant-refrigerant compatibility, thermal stability tests, and the inclusion of nanoparticles to enhance lubricant properties. Results indicate that synthetic lubricants, which now account for over 50% of usage in refrigeration system, exhibit up to 30% better thermal stability and 25% improved chemical resistance compared to mineral oils. Nanoparticles, such as SiO2 and TiO2, were found to improve thermal conductivity by 10-15%, significantly enhancing system efficiency. The study concludes that selecting appropriate synthetic lubricants and incorporating nanoparticles can substantially improve the performance and sustainability of modern refrigeration systems.